IDENTIFICATION OF YEASTS ISOLATED AT THE ANIL WASTEWATER TREATMENT PLANT IN SÃO LUÍS, BRAZIL (PRÁXIS EM SAÚDE, 2026)
Wastewater Treatment Plants (WWTPs) are fundamental to maintaining basic sanitation, and the regularity of their operations is of utmost relevance to public health. The present study aims to understand key information regarding the pathogenicity of yeasts isolated from the Anil WWTP in São Luís, Maranhão. Samples were obtained from different operational stages of the Anil WWTP, followed by isolation, identification by MALDI-TOF, and preservation. This study highlights the main findings of the isolation, including C. parapsilosis, C. tropicalis, C. glabrata, C. krusei, C. metapsilosis, and H. opuntiae, as well as the main conclusions regarding the epidemiology and pathogenicity of these yeasts, considering the presence of C. parapsilosis and C. tropicalis on the WHO Fungal Priority Pathogens List (FPPL). Finally, further in-depth studies on the virulence and clinical aspects of the identified yeasts are suggested, as well as assessments of the impact of these microorganisms on public health in São Luís.
Keywords: MALDI-TOF; WHO; FPPL; Wastewater